Analysis of Torque Loading System based on Hydraulic Energy Closed-loop - Xianjin Shi; Gang Sun; Hongqi Liu (Institute of Advanced Engineering and Science, 2013)
Power head with high power and large torque is the main power equipment of the rotary drilling rig. Aimed at the working condition, energy saving torque loading test program of power head was put forward and mathematical and simulation models of hydraulic energy closed-loop torque loading system were established. Combined with bond graph and state equations of torque loading system with single pump, effect of the logical relationship of discharge between the driving motor and loading pump and the relationship between the adjusting proportion of series and parallel pressure on the torque loading system was analyzed because both hydraulic flow and pressure can have an influence on the system stability. It proves that the torque loading system is stable when the adjusting proportion of series pressure is larger than that of the parallel pressure. Otherwise, it needs to consider the discharge trend between the power motor and loading pump. DOI: http://dx.doi.org/10.11591/telkomnika.v11i12.3052